2017
DOI: 10.1111/hdi.12587
|View full text |Cite
|
Sign up to set email alerts
|

The nature, consequences, and management of neurological disorders in chronic kidney disease

Abstract: Perhaps no other organ in the body is affected as often and in as many ways as the brain is in patients with chronic kidney disease (CKD). Several factors contribute to the neurological disorders in CKD including accumulation of uremic toxins, metabolic and hemodynamic disorders, oxidative stress, inflammation, and impaired blood brain barrier among others. The neurological disorders in CKD involve both peripheral and central nervous system. The peripheral neurological symptoms of CKD are due to somatic and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 77 publications
2
51
0
7
Order By: Relevance
“…21 Kidney dysfunction is associated with AF, AF-related comorbidities (including stroke), response to targeted therapies for AF, as well as cognitive decline and dementia. [22][23][24][25][26][27] Highlighting the vascular, kidney, and brain connection, the presence of vascular nephropathy was independently associated with a 15-fold increase in white matter changes found by cranial imaging in a study of 52 patients with chronic kidney disease. 26 As more biomarkers of vascular health are surveyed that involve multiple pathways of vessel physiology, the strength of the association with cerebral vascular injury increases.…”
Section: Discussionmentioning
confidence: 99%
“…21 Kidney dysfunction is associated with AF, AF-related comorbidities (including stroke), response to targeted therapies for AF, as well as cognitive decline and dementia. [22][23][24][25][26][27] Highlighting the vascular, kidney, and brain connection, the presence of vascular nephropathy was independently associated with a 15-fold increase in white matter changes found by cranial imaging in a study of 52 patients with chronic kidney disease. 26 As more biomarkers of vascular health are surveyed that involve multiple pathways of vessel physiology, the strength of the association with cerebral vascular injury increases.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease is frequently associated with neurological disorders affecting both peripheral and central nervous system resulting in behavioral abnormalities, including mental and cognitive dysfunctions (28)(29)(30). It has been shown that mild CKD may lead to activation of limbic system, central sympathetic, stress-and pain-related brain areas (31).…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, hypertensive encephalopathy can progress to cerebral hemorrhage, coma, and death. Other underlying conditions associated with elevated blood pressure such as kidney disease and diabetes are common comorbidities in severe COVID-19 cases and can also contribute to the occurrence of encephalopathy and seizures (103,104).…”
Section: Pre-existing Hypertension and Other Neurological Manifestatimentioning
confidence: 99%